2020
DOI: 10.3390/molecules25245931
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Hexaphosphate (IP6) and Colon Cancer: From Concepts and First Experiments to Clinical Application

Abstract: Multiple human health-beneficial effects have been related to highly phosphorylated inositol hexaphosphate (IP6). This naturally occurring carbohydrate and its parent compound, myo-inositol (Ins), are abundantly present in plants, particularly in certain high-fiber diets, but also in mammalian cells, where they regulate important cellular functions. However, the striking and broad-spectrum anticancer activity of IP6, consistently demonstrated in different experimental models, has been in a spotlight of the sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 72 publications
(130 reference statements)
0
21
0
1
Order By: Relevance
“…In contrast, phytic acid increased the size of aggregates under the action of agonists [ 49 ]. The authors of [ 50 ] suggested that inhibition of agonist-induced platelet aggregation promoted the treatment of oncological diseases by the example of colon cancer. We can assume that the inhibition of aggregation under the action of BDP and ZnO NPs-BDP, in which phosphate groups are ionized, will promote the healing of burn wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, phytic acid increased the size of aggregates under the action of agonists [ 49 ]. The authors of [ 50 ] suggested that inhibition of agonist-induced platelet aggregation promoted the treatment of oncological diseases by the example of colon cancer. We can assume that the inhibition of aggregation under the action of BDP and ZnO NPs-BDP, in which phosphate groups are ionized, will promote the healing of burn wounds.…”
Section: Discussionmentioning
confidence: 99%
“…This function has also been highlighted in the context of food processing; research is being conducted on the use of phytic acid supplementation to suppress oxidation that may occur during food processing [ 61 , 68 ]. Moreover, people with a higher intake of grains and vegetables containing large amounts of phytic acid have a lower incidence of colorectal cancer, due to phytic acid activating the expression of tumor-suppressor genes (e.g., p53 and WAF-1/p21) [ 71 , 72 ]. Phytic acid also exhibits antitumor activity by reducing cancer cell proliferation and increasing cell differentiation ( Figure 7 ) [ 71 ].…”
Section: Phytic Acidmentioning
confidence: 99%
“…Moreover, people with a higher intake of grains and vegetables containing large amounts of phytic acid have a lower incidence of colorectal cancer, due to phytic acid activating the expression of tumor-suppressor genes (e.g., p53 and WAF-1/p21) [ 71 , 72 ]. Phytic acid also exhibits antitumor activity by reducing cancer cell proliferation and increasing cell differentiation ( Figure 7 ) [ 71 ]. In addition, lower inositol phosphates, such as IP3 and IP4 (containing three and four phosphorus groups, respectively) play an important biological role in regulating cell-to-cell responses and are known to act on the signaling systems in the body [ 73 ].…”
Section: Phytic Acidmentioning
confidence: 99%
“…A few clinical studies have shown that IP 6 alone or in combination with Ins is able to enhance the anticancer effect of conventional therapy, control cancer metastases, and improve quality of life. The historical perspectives, from the first experiments, concepts, and hypotheses to the first clinical observation in colon cancer patients is presented here [ 8 ], and that was the base of several clinical trials conducted later [ 9 ]. It is important that the prior research in the field is recognized and that credits are attributed properly.…”
mentioning
confidence: 99%
“…To better understand the molecular mechanisms of the anticancer action of IPs, Kapral et al conducted the study on the involvement of microRNAs and showed that IP 6 exerted its biological functions by downregulating the miR-155 expression in human colon cancer cells [ 11 ]. However, the synergistic effect of IP 6 and Ins was observed not only in cancer [ 8 ] but also in metabolic diseases. This combination has been beneficial in regulation of insulin secretion and was effective in the management of type 2 diabetes mellitus [ 12 ].…”
mentioning
confidence: 99%